Studying some aspects of the viking age in english-language historiography - D.G. Smyattskij (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки, 2024)
Background. The topic of the research is relevant due to the fact that Russian scholarship has so far paid little attention to the problem of updating the historiographical experience of English-language authors on the particular issues of the Viking Age. A com-prehensive analysis of this material will make it possible to supplement the body of ideas about the Normans, and to define their role and significance in history. The purpose of the study is to update the historiographical material, which can provide a new round of develop-ment of Russian historical thought by analysing and taking into account the interpretation of historical events of the Viking Age, identifying the features of scientific views and the meth-ods of research used by English-language authors. Materials and methods. To achieve these objectives, it is expedient to use the methods of comparative analysis and synthesis, which allowed us to study the historical works of English-language authors and to compare their results with the achievements of Russian historiography. Results. The contents of historical works by English-language authors on the Viking Age have been researched, highlighting the main aspects of the study this period, identifying the sources used, the approaches and methodology used, and the features of the presentation of the material. Conclusions. In the research of English-language authors on the Viking Age, special attention is paid to the Nor-man raids and the Scandinavian colonization of England and the West Frankish kingdom, their causes, objectives and the changing nature over time. The historiography under consid-eration has extensively studied the processes of interaction between Anglo-Saxon and Scan-dinavian societies and has clearly defined the significance and role of Norman expansion in British history. In addition, English-language authors in their research on the Viking Age used a wide range of sources, applying an interdisciplinary approach, narrative, diachronic, historical-comparative and other methods in their study.